Achieving Sustainable Food Systems in a Global Crisis: Malawi - Bizikova, Livia; de Brauw, Alan; Rose, Mali Eber; Laborde Debucquet, David; Motsumi, Kulthoum; Murphy, Mike; Parent, Marie; Picard, Francine; Smaller, Carin (IISD, 2022)
This report presents an evidence-based and costed country roadmap for effective public interventions to transform agriculture and food systems in Malawi in a way that ends hunger, makes diets healthier and more affordable, improves the productivity and incomes of small-scale producers, and mitigates and adapts to climate change. The report is part of a project that explores the interaction between achieving healthy diets, reducing hunger and poverty, and addressing climate change within the evolving food systems in three countries—Ethiopia, Malawi, and Nigeria.